Presenting the fintech market development model with an emphasis on existing challenges and strategies - Seyed Mani Sadraee; Farideh Haghshenaskashani; Mehdi Karimizand (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research is to present the fintech market development model with an emphasis on existing challenges and strategies. The research method is applicable in terms of purpose, thematic analysis type in terms of execution method (qualitative-quantitative), fundamental in terms of its nature, and exploratory-correlative in terms of data collection method. The statistical population of the research includes 20 managers and experts of fintech companies active in the field of payment with the license of Shaperk, including Zarinpal, Asan-Dariaft, Balle Financial Messenger, EasyPay, Iranian credit and point cards. The sampling method is done in a judgmental manner, and the interviews continued until reaching theoretical saturation. The method of data collection and analysis is interview and thematic analysis in the qualitative part, and questionnaire and content validity technique (CVR) and semi-structured interview data collection tool in the quantitative part. The results of the research showed that the challenges of fintech market development include insufficient infrastructure, regulatory and legislative barriers, difficulty of working with public/general customers, mistrust of technology and fintech, low levels of income and product pricing challenges, and cultural barriers. Also, fintech market development strategies include community participation in the marketing process, use of social networks, smart and optimal advertising, useful and valuable content production, branding, adaptation of communication strategies to the nature of the fintech market, geographic and cultural segmentation of the market, and also training to the customer. Extended Abstract Introduction Every day, people see a lot of advertisements everywhere; from bus stop, street banner, shopping mall to magazine, TV, computer, mobile etc. However, more often than not, these ads feel like annoying information that the general public is forced to see. For this reason, professional marketers need to redefine their marketing idea. They should understand that marketing is not only about sales and advertising, but also fulfills customer needs in order to overcome constraints (Sheth & Parvatiyar, 2021). On the other hand; with the digital trend, the financial sector has started to apply and implement technology in its workflow. More and more start-ups have formed to provide digital financial services. Some of the companies that provide online payment gateway are pioneers in this field which is widely used all over the world. In addition, more and more investors are spending on new technologies; they are competing with each other in an effort to improve security and user convenience. Financial technology companies are trying to attract users with new mobile phone features, capabilities and technologies. Recently, the blockchain concept has also opened new solutions for security issues; therefore, fintech tools have become the most popular digital services and have the largest share of fintech stocks worldwide (Fernandez-Vazquez et al, 2019). In the meantime, financial technology (Fintech) as a technological innovation has been considered especially important for the development path of countries. This is due to its potential to promote financial inclusion so that more people can access financial services (Demirguc-Kunt et al, 2018). Based on this, the current research is looking for an answer to this question: What is the fintech market development model with an emphasis on existing challenges and strategies? Theoretical Framework marketing strategy When companies enter a new market, they will most likely face thousands of challenges and risks related to establishing their operations and acceptance of their offers by new customers, and the company will compete for market share with other companies that already have supply chains, distribution channels and already established customer bases (Luo, 2022). Foreignness, geographic distance, and characteristics of the home market all contribute to these challenges in new markets. This issue applies more in emerging markets such as fintech (Khan & Khan, 2021). In this regard, Gaur et al, (2011) argue that emerging market challenges lead to higher external liability. These challenges include large heterogeneous populations with low incomes, inadequate infrastructure, lack of resources, corruption, and in general, with structural flaws (Barnard & Luiz, 2018). From the point of view of marketing strategy, companies adapt their marketing strategies to achieve a competitive advantage when entering a new market. Once a company has decided to expand into a new market and adopt its marketing strategy, the question of what changes will be necessary for this particular context will arise. In this regard, Sharmelly & Klarin (2021) described implicit concepts for segmentation, product variety, pricing, distribution, and communication methods of the company. They argue that segmentation costs are high, and that mass media marketing is not well adapted to emerging markets. Also, the offered products need to be functional and also made to not become obsolete quickly. Shadbakhsh (2023) investigated the impact of using sustainable marketing strategies on the performance of digital businesses with the mediation of information technology in the country's real estate industry. The results showed that marketing trends and sustainable marketing experiences have a positive effect on the performance of the studied companies. Also, marketing trends, sustainable marketing experiences, and sustainable marketing strategies have a positive effect on the performance of selected companies. Barrio Oton (2021) in a research investigated the social media marketing in the fintech ecosystem in Monfer Startup Company. For this purpose, a detailed study of the fintech private equity industry was conducted through Porter's 5 forces model, along with an explanation of the Monfer startup case through the blue ocean strategy canvas. Then, secondary data including statistical insights were collected directly from the company. This study was further designed by analyzing the internal and external situation and concluded with a strategic planning model and setting goals through the framework of smart goals. Research methodology The research method is applicable in terms of purpose, thematic analysis type in terms of execution method (qualitative-quantitative), fundamental in terms of its nature, and exploratory-correlative in terms of data collection method. The statistical population of the research includes 20 managers and experts of fintech companies active in the field of payment with the license of Shaperk, including Zarinpal, Asan-Dariaft, Balle Financial Messenger, EasyPay, Iranian credit and point cards. The sampling method is done in a judgmental manner, and the interviews continued until reaching theoretical saturation. The data collection tool is a semi-structured interview. Research findings For data analysis, thematic analysis was used in the qualitative part, and content validity technique (CVR) was used in the quantitative part. The results of the research showed that the challenges of fintech market development include insufficient infrastructure, regulatory and legislative barriers, difficulty working with public/general customers, mistrust of technology and fintech, low levels of income and product pricing challenges, and cultural barriers. Also, fintech market development strategies include community participation in the marketing process, use of social networks, smart and optimal advertising, useful and valuable content production, branding, adaptation of communication strategies to the nature of the fintech market, geographic and cultural segmentation of the market, and training to the customer. Conclusion The current research has been carried out with the aim of presenting the fintech market development model with an emphasis on existing challenges and strategies. The results of the present research is aligned with the results of Shadbakhsh (2023), Barrio Oton (2021), Pazhoheshfar & Biabani (2021), Hammerschlag et al, (2020), Nurjanah et al, (2020), and Noami et al, (2019). The results of Shadbakhsh (2023) showed that marketing trends and sustainable marketing experiences have a positive effect on the performance of the studied companies. Also, marketing trends, sustainable marketing experiences and sustainable marketing strategies have a positive effect on the performance of selected companies. According to the results of the research, the following suggestions were presented: Effective market development strategies often require local community involvement in marketing, product distribution and product awareness. In general, using local people to distribute products is important to the success of a marketing strategy. Local people understand the nuances of the market and can help distribute products in the most efficient and cost-effective way. Finding local people often has to be done through field research, but can also be achieved through networking. The reason for this is that the community plays a major role in Iranian culture and people are more likely to use a product if it is approved by a member of the community. In creating consumer awareness, community participation can be in the form of in-person or online campaigns (for example through social media). When talking about the development of the fintech market, it means that it should be possible to identify that part of the target market and, according to the knowledge that is found, convert the audience of social networks into customers of your market. Fintech companies can advertise their products or services with an optimized website or a standard page according to the Instagram algorithm. The cost of such advertisements is much lower and the efficiency of advertisements is high. Therefore, producing valuable content helps clarify the topic in the audience's mind. For example, producing content that is according to the taste and interest of the young generation can have a great impact on the success of the company. If you can start producing content according to the type of audience that exists, you will get a lot of success and fame in business.